Medical students’ perception on fecal microbiota transplantation - Petru C. Madar; Oana Petre; Adriana Baban; Dan L. Dumitrascu (BMC Medical Education, 2019)
Abstract Background Fecal microbiota transplantation (FMT) has become an emergent method in the therapy of several intestinal diseases, mainly in Clostridium difficile recurrence. The training of FMT in medical schools is at its beginning and in countries where FMT is only occasionally carried out, it is important to know the perception of medical students on FMT. Methods We undertook a survey of 3rd year medical students not exposed to official academic information on FMT in order to find out their knowledge, beliefs and attitude toward FMT. A number of 80 students were asked to fill a dedicated online questionnaire. Results 52 out of 80 third year medical students anonymously filled the questionnaire (65% response rate). 34% of respondents reported to have at least a medium level of knowledge regarding FMT. The top indication for FMT identified by 76.9% was C. difficile infection; however, 60% believed FMT to be a promising therapy for a high number of conditions and while almost all respondents (98.1%) would recommend it, 88.4% would explore other options first. Colonoscopy was considered the optimal method of delivery by 42.3%. Only 39% of participants believed that patients would accept FMT, however 71% considered that a more socially acceptable name for the procedure and anonymous donors would increase acceptance rate. The risk of transmitting a disease undetected by donor stool screening procedures to the recipient was the most worrying side effect considered by 75% of respondents. 54% believed that more research is required for FMT to enter clinical practice and 55.7% of respondents would enroll patients in controlled clinical trials. Conclusions Medical students not exposed to educational information on FMT seem to be somewhat well informed about this method and would recommend it to their patients. Students, however, need to know more on the indications of FMT.